The relevance of universities Ombudsman framework in Malaysia - Omoola, Sodiq (2019)
Complaint handling metrics have become a vital component of modern education system around the world. In highly educated environments such as universities, conflict appears to be inevitable among stakeholders, i.e. students, staff, and the administration. The uncertainty surrounding the appropriate mechanism for dispute resolution within Malaysian universities seems apparent as the, Legal adviser, deputy deans and deans of faculties compete for authority over initial dispute resolution points. Availability of effective, transparent and fair complaint management process is capable of increasing student enrolment and satisfaction particularly for international students in Malaysia. In Malaysia, few universities have identified the need to have a robust effective, independent and ombudsman office as an internal mechanism for dispute between and among students, staff and other stakeholders in the university community. This paper will explore the legal basis for Ombudsman scheme established in Malaysian universities with special reference to the Universiti Sains Malaysia (USM) and Monash University Malaysia. Beyond the traditional feedback mechanisms and quality assurance measures, the paper recommends an ombudsman regulatory framework for the ministry of higher education and the Malaysian university system.